WARISAN FILSAFAT ISLAM DI KOTA FEZ DAN SUMBANGSIHNYA BAGI MASYARAKAT INDONESIA - Sairah, Abdul Rokhmat (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2023)
This article aims to reveal the Islamic philosophy legacies in Fez City, Morocco, and analyze the values ​​relevant to Indonesian people’s lives. Fez is one of the centers for the development of Islamic philosophy in the golden age of Islamic civilization. Fez is located in the modern state of Morocco, Fez is the spiritual and cultural capital of Morocco. Fez has historical dynamics until it developed into the modern city today, but Islamic philosophy colors the city's history. This article is the result of research by the author on the visit to the city from October to mid-November 2019. This research is an observation and literature study. Data analysis used historical and phenomenological approaches. The results of this study indicate that the legacies of Islamic philosophy could be found in the Fez in tangible and intangible forms. The tangible legacies are the Al-Karaouine University Architectural Building, and works of Islamic philosophers who have intersected with Fez, including Ibn Khaldun, Averroes, Avempace, and Moses Maimonides. The intangible legacies are the education system, a spirit of freedom of thinking, and tolerance. These legacies could be an alternative reference for the Indonesian Muslim society to develop behavior in daily life with tolerance, freedom of thinking, and an education system.